Collection, storage and use of blood samples for future research: views of Egyptian patients expressed in a cross-sectional survey. Issue 9 (26th July 2010) - Abou-Zeid, Alaa; Silverman, Henry; Shehata, Magdi; Shams, Mohamed; Elshabrawy, Mervat; Hifnawy, Tamer; Rahman, Safa Abdel; Galal, Bahiga; Sleem, Hany; Mikhail, Nabiel; Moharram, Nadia
Abstract : Objective: To determine the attitudes of Egyptian patients regarding their participation in research and with the collection, storage and future use of blood samples for research purposes. Design: Cross-sectional survey. Study population: Adult Egyptian patients (n=600) at rural and urban hospitals and clinics. Results: Less than half of the study population (44.3%) felt that informed consent forms should provide research participants the option to have their blood samples stored for future research. Of these participants, 39.9% thought that consent forms should include the option that future research be restricted to the illness being studied. A slight majority (66.2%) would donate their samples for future genetic research. Respondents were more favourable towards having their blood samples exported to other Arab countries (62.0%) compared with countries in Europe (41.8%, p<0.001) and to the USA (37.2%, p<0.001). Conclusions: This study shows that many individuals do not favour the donation of a blood sample for future research. Of those who do approve of such future research, many favour a consent model that includes an option restricting the future research to the illness being studied. Also, many Egyptians were hesitant to have their blood samples donated for genetic research or exported out of the Arab region to the USA and European countries. Further qualitative research should be performed to determine the underlying reasons for many of our results.